Data Basic Information System Based On Accreditation Based On Trunojoyo Madura University - moch nasrul ulum; moch kautsar sophan (Universitas Trunojoyo Madura, 2017)
The accreditation program of undergraduate study is an evaluation process which is done periodically by a body that has the authority i.e. the BANPT. The implementation of the process of preparing the accreditation program of study form of some organizations which play a role in manage and supply the data needs of the accreditation form. The data used by the program to study the process of preparation of the accreditation form is historical data collected periodically from time to time in order to give an overview of the activities/information. The process of collecting the scattered data from each of these organizations require great resources and time briefly. The system used a course at University in conducting the Madura Trunojoyo gathering historical data accreditation by searching, collecting and recording the data in its own separate list and yet maximally computerized and centralized yet most of the management and the management of its data. So it developed a system that can muster such data i.e. Information System Database-based Accrediting University Trunojoyo Madura .